(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Autoimmune hepatitis (AIH) is a chronic and progressive inflammatory disease of unknown etiology, characterized by immune system-mediated damage to the liver parenchyma, hypergammaglobulinemia, and the appearance of tissue-specific autoantibodies. Today, a global increase in the prevalence of AIH is observed in internal medicine clinics. Because the disease often begins latently or with non-specific symptoms (asthenia, arthralgia, dyspepsia), patients present to a general practitioner or gastroenterologist late—at the stage of established liver cirrhosis. Therefore, early diagnosis and proper differential diagnosis at the primary healthcare level remain an urgent problem.